Transformasi Digital Pemerintahan Desa di Era Society 5.0 - Asep Mulyadi; Pakhudin Pakhudin (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2026)
The digital transformation of village government in the Society 5.0 era is one of the government's efforts to improve the quality of public services and village governance based on information technology. This study aims to determine the implementation of digital transformation in village government, supporting and inhibiting factors, and its impact on public services and village governance. This study uses a qualitative research method with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation. Research informants consisted of village heads, village officials, village information system operators, and the community. The results show that digital transformation in village government has been implemented through the use of the Village Information System (SID), digital-based administrative services, village websites, and social media as a means of public information. The implementation of this digitalization can increase the effectiveness of public services, accelerate administrative processes, increase government transparency, and facilitate the public in obtaining information and village services. Supporting factors for digital transformation include government support, technology availability, village apparatus competence, and community participation. Meanwhile, inhibiting factors include limited internet infrastructure, low digital literacy, budget constraints, and the lack of technological capabilities of village apparatus. Based on the research results, the digital transformation of village government in the Society 5.0 era has an important role in creating a more effective, efficient, transparent, and responsive village government to community needs.